2007
DOI: 10.1111/j.1365-313x.2007.03287.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet delivery – sugar translocators as ports of entry for antisense oligodeoxynucleotides in plant cells

Abstract: SummaryAntisense oligodeoxynucleotides (ODNs) are short (12-25 nt long) stretches of single-stranded DNA that may be delivered to a cell, where they hybridize to the cognate mRNA in a sequence-specific manner, thereby inhibiting gene expression. Here we used confocal microscopy to monitor the uptake and trafficking of ODNs in barley tissues. We conclude that uptake of ODNs across the plant plasma membrane is mediated by active transport of mono-or disaccharides through sugar translocators. We demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 25 publications
0
26
1
1
Order By: Relevance
“…When testing the effect of different sugars, we found no evidence for enhanced uptake (data not shown). This result contrasts with the observation of Sun et al (2005Sun et al ( , 2007 that the uptake by barley (Hordeum vulgare) leaves of the SUSIBA2 transcriptional factor antisense ODNs was promoted by high concentrations of Suc (200 mM). During our preliminary experiments, we found that wheat, the spring cv CY-45 in particular, was sensitive to osmotic stress, which could already be observed in the presence of 200 mM Suc.…”
Section: Odn Application and Deliverycontrasting
confidence: 93%
See 1 more Smart Citation
“…When testing the effect of different sugars, we found no evidence for enhanced uptake (data not shown). This result contrasts with the observation of Sun et al (2005Sun et al ( , 2007 that the uptake by barley (Hordeum vulgare) leaves of the SUSIBA2 transcriptional factor antisense ODNs was promoted by high concentrations of Suc (200 mM). During our preliminary experiments, we found that wheat, the spring cv CY-45 in particular, was sensitive to osmotic stress, which could already be observed in the presence of 200 mM Suc.…”
Section: Odn Application and Deliverycontrasting
confidence: 93%
“…In itself, it is also an advantage that ODN-treated plants would not be genetically modified organisms; therefore, no special measures would be required during cultivation and transportation. Sun et al (2005Sun et al ( , 2007 were the first to apply ODNs in green leaves: antisense ODNs with their natural structure were used to inhibit the expression of SUSIBA2, a transcription factor involved in starch synthesis. The direct application of nucleic acids in plant tissues was then suggested to open the way for high-throughput screening for gene function (Roberts, 2005), but the use of this technique in plant science fell short of expectations.…”
mentioning
confidence: 99%
“…The low cell-wall permeability has traditionally limited the development of inhibition via asODNs in plant biology studies; nevertheless, a growing interest arose when the uptake of synthetic asODNs was demonstrated to be enhanced in sugar solution, as the uptake probably occurs through sugar transporters (Sun et al, 2007;2008;Xie et al, 2014 [30-32]). Similarly, patent application WO2013089614A1 [33] describes the use of an aqueous-sugar solution conveying an antisense oligodeoxinucleotide capable of hybridizing to a portion of mRNA transcribed from an essential plant gene, knocking it down, and thus acting as a herbicide.…”
Section: Antisense Technologiesmentioning
confidence: 99%
“…Short stretches of 12–25 nucleotide long single-strand sequences have been delivered to barley leaf cells to block the effect of SUSIBA2, a key transcriptional activator involved in plant sugar signaling [73]. Recently, this approach has been successfully implemented to deliver antisense oligodeoxynucleotides to barley seed endosperm to suppress sugar related signaling genes [74]. HvGAMYB, a transcription factor initially identified in aleurone and shown to be upregulated by gibberellin, has been shown to be expressed also in barley anthers.…”
Section: Functional Genomics Approaches In Barleymentioning
confidence: 99%